Synthesis, Biological and Pharmacological Activities of Some New Derivatives of 5-Aryl-1,3,4-thiadiazolin-2-thiones - Aruna Devi, M.; Reddy, V.M. (Asian Journal of Chemistry, 2010)
Two different S-(5-aryl-1,3,4-thiadiazol-2-yl)mercapto acetic acids were synthesized from the respective 5-aryl-1,3,4- thiadiazolin-2-thiones on reaction with chloroacetic acid. Each of these acids has been converted in situ into acid chloride using thionyl chloride and condensed with three different seecondary amines viz., dicyclohexylamine, morpholine and piperidine. The products obtained in each case were purified and characterized as the respective N,N-disubstituted S-(5-aryl- 1,3,4-thiadiazol-2-yl)mercaptoacetamides. Alternatively the in situ acid chlorides were allowed to react with 2-methoxyethanol and 2-ethoxyethanol. These products have been purified and characterized as the respective esters, i.e., 2-alkoxyethyl S-(5-aryl-1,3,4-thiadiazol-2-yl)mercaptoacetates. Similarly, the acid chlorides in situ have been also allowed to react with two different N-substituted aminoethanols and the products were characterized as the respective 2-N,N-substituted aminoethyl S-(5-aryl-1,3,4-thiadiazole-2-yl)-mercaptoacetates. All the three types of new derivatives of 5-aryl-1,3,4-thiadiazolidin- 2-thiones were assayed for their antibacterial, antifungal, antihistaminic and anticholinergic activities by standard methods.